Respostas fisiológicas e anatômicas de Billbergia zebrina Lindl. (bromeliaceae) em função de fontes e concentrações de carboidratos durante o cultivo in vitro convencional - Santos, Elizangela Rodrigues (2018)
When propagated in vitro, the explants receive all the nutrients necessary for their growth, including the carbohydrate source through the culture medium. However, it is not well understood how the carbohydrate source and concentration may affect the functionality of the photosynthetic apparatus (mainly photosystem-PSII) of these plants. The objective of this study was to evaluate the physiological and anatomical responses of Billbergia zebrina (Herbert) Lindley (Bromeliaceae) as a function of sources and concentrations of carbohydrates during in vitro culture. Lateral shoots of preestablished and in vitro multiplied plants were individualized and transferred to 268 ml flasks with 50 ml of MS medium containing fructose, glucose and sucrose in four concentrations (0, 15, 30 and 45 g L-1 ). After 55 days of cultivation, transient chlorophyll a fluorescence, anatomical leaf analysis and growth analysis were evaluated. The in vitro conditions influenced the photosynthetic and anatomical performance of plants of Billbergia zebrina. The concentration range between 15 and 30 g L-1 of sucrose did not cause major changes in the performance of the photosynthetic apparatus and in the anatomy of the plants, proving to be more efficient. The concentration and type of carbohydrate used during in vitro culture does not diminish the performance of the photosynthetic apparatus. When grown at concentrations of 15 and 30 g L-1 independent of the carbohydrate used, the plants presented higher stomatal density. Supplementation of the culture medium with monosaccharides caused alterations in the development of xylem vessels, such as the increase in number and vessel diameter, allowing adaptation to microenvironmental conditions. The increase of the fresh mass was verified as a result of the increase of the carbohydrate concentration added in the medium, followed by a decrease when grown with 45 g L-1 (glucose and sucrose).